The Physical Fitness Gap between Strikers and Defenders in Football Extracurricular Programs - Darmawan, Adriana Galih; Suharjana, Suharjana (Universitas Pendidikan Indonesia, 2019)
This research can be categorized as a comparative descriptive study conducted through a survey to measure physical fitness. The subjects of this study were the students who joined the football extracurricular program in the State Junior High School 3 Sleman that consisted of 14 strikers and 23 defenders. The research instrument used the physical fitness test. The data analysis technique employed t-test analysis that required normality test and homogeneity test with 5% significance level. The results showed t countÂ 3.956 with t table 2.027 (3.956 2.027). It means that there is a significant physical fitness difference between strikers and defenders in the football extracurricular program. The average physical fitness for strikers was 14.57, while the average physical fitness of defenders was 12.04. Based on the research findings, it can be concluded that there is a significant physical fitness difference between the strikers and the defenders in the football extracurricular program in the State Junior High School 3 Sleman